IMPLEMENTASI KURIKULUM TERPADU BERBASIS AKHLAQUL KARIMAH DI SDIT TAHFIZH QURAN AL-JABAR KECAMATAN TELUK JAMBE BARAT KARAWANG JAWA BARAT - Sabrowi; Abdul Khoir, HS; Asep Dudin Abdul Latip (Fakultas Tarbiyah Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
The background of the problem in the research is how to provide motivation, advice and encouragement so that students/students learn again at home with parental guidance. Attending children's recitations at the Majlis Ta'lim or Musholla (ba'da Magrib). organized by ustadz or ustadz. The addition of school hours not only (4JP/Sunday). With the addition of Islamic Religious Education sub-subjects, schools require students to carry out Duha Prayers according to a certain schedule. The purpose of the study was to determine the planning of implementing an integrated curriculum based on morality in Integrated Islamic Elementary Schools, implementing an integrated curriculum based on morality, knowing the supporting and inhibiting factors in implementing an integrated curriculum based on morality. The research was conducted at the Integrated Islamic Elementary School (SDIT) Tahfizh Qur'an Al-Jabar, Telukjambe Barat District–Karawang, West Java, Research Qualitative research, case study method, a research procedure that produces descriptive data in the form of written or oral data from people and observable behavior as research objects. by observing, reviewing documents and interviews. The results of the study are the quantity of education in terms of the presence or graph of student progress from year to year increasing more and more, the quality/quality of education is quite good and gains recognition/trust from the community, so that many parents send to this SDIT, the school is accredited with an A grade, although first time Following the accreditation, the students always excel in winning 1st, 2nd and 3rd place in each branch of the competition in participating in the District Level PAI Performance Competition organized by the PAI KKG, and even winning the overall winner.